Influence of π-linker on triphenylamine-based hole transporting materials in perovskite solar cells. (April 2017) - Liu, Xuepeng; Kong, Fantai; Guo, Fuling; Cheng, Tai; Chen, Wangchao; Yu, Ting; Chen, Jian; Tan, Zhan'ao; Dai, Songyuan
Abstract: In this work, three simple hole transporting materials containing a thiophene, thieno [3, 2-b]thiophene (two fused thiophene rings) or a dithieno[3, 2-b:2′, 3'-d]thiophene (three fused thiophene rings) as π-linker substituted by 4′, 4″-dimethoxytriphenylamine donor groups are presented. The influence of increasing fused thiophene rings of π-linker in new compounds on the photophysical, electrochemical, thermal properties, hole mobility and photovoltaic performance in perovskite solar cells are investigated. The compound, in which dithieno[3, 2-b:2′, 3'-d]thiophene act as π-linker, shows better hole mobility and higher thermal stability than the compounds that contain thiophene or thieno [3, 2-b]thiophene π-linker. Due to the improved hole mobility and superior hole extraction ability of the compound which contains dithieno[3, 2-b:2′, 3'-d]thiophene π-linker, the perovskite solar cells based on it achieve higher J sc, V oc and FF values than the devices based on the other two compounds. These results indicate that the increasing fused thiophene rings of π-linker in hole transporting materials can be helpful to develop efficient perovskite solar cells. Graphical abstract: The performance the perovskite solar cells improved with the increasing fused thiophene rings of π-linker in new hole transporting materials. Highlights: Three new hole-transporting materials with different π-linker are developed. Hole mobility and the performance improve with the increasing fused thiophene rings of π-linker in HTM. The dithieno[3, 2-b:2′, 3'-d]thiophene-based device show best performance.